(untitled) (Bangladesh Journal of Anatomy, 2010)
Context: Gentamicin is an antibiotic used in gram-negative infection. It is an nephrotoxic agent. Proximal tubular epithelial cells are selectively sensitive to gentamicin. Objective: To observe the toxic effect of gentamicin on epithelial cells of proximal convoluted tubule in Long Evans rats. Study design: An experimental study. Plan and period of study: The study was carried out in the Department of Pharmacology of IPGMR Dhaka during the period of 1995 to 1996. Materials and methods: Eighteen mature long Evans rats were divided into three groups A, B & C. The rats of group A were treated with vehicle and group B and C were treated with gentamicin 50gm and 100gm respectively. Blood urea and serum creatinine were measured and microscopic damaged cells were counted. Result: There was significant increase in serum creatinin and blood urea in gentamicin treated groups. Microscopic examination of kidney showed necrosis of proximal tubular cells. Conclusion: It can be concluded from this study that gentamicin has toxic effects on renal tubule. Key words: Gentamicin. DOI: 10.3329/bja.v7i2.6088 Bangladesh J. Anat. 2009; 7(2) :84-86